PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN SEDERHANA SISWA KELAS III SDN 128 PEKANBARU - Ridawati '; Gustimal Witri; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is motivated by the fact that is faound in class III A SDN 128 Pekanbaru, which  shows the results of learning in Indonesian is still relatively low. Formulation the problem is this research is.”How to improve the activity of essay writing simple  students in grade III of SDN 128 Pekanbaru through Picture and picture ?”. This research aims to improve learning outcomes in Indonesian studentsof SDN 128 Pekanbaru witch application of learning models cooperative  picture and picture, The hypotesis of this study is that if applied learning model cooperative  picture and  picture it can improve learning outcomes improve the activity of essay writing simple  students in students in grade III of SDN 128 Pekanbaru. This study was conducted in SDN 128 Pekanbaru in April dan Mei 2016. This from is research is classroom action reserach (PTK) are planned as mus as two cycle. The subjects were students of class III A SDN 128 Pekanbaru academic year 2015/2016 which amounted to 38 people consisting of 20 men and 18 women. Based on the results of research of teacher activity sheet seen rising each meeting. At the first meeting of the first cycle 67,5%, the second meeting of the first cycle of  75%, at the three meeting of the second cycle of 87,5%, and the fourth meeting of the second cycle of  97,5%. Student activity observation sheet also increased at every meeting. At the first meeting of the first cycle of 65,6%, the second meeting of the first cycle of 78,1%, at the three meeting of the second cycle of 87,5%, and the fourth meeting of the second cycle of 93,7%. Mastery learning outcomes to repeat at first cycle increased 52,6%  from the base score of 86,8%. In the second cycle increased by 61,7%. UH then the first cycle to 69,2% with an increase of 12,16% . Where as the second cycle of the average value of UH becomes 79,3%. Where as the second cycle of the average value.  Key Words : Cooperative learning model piture and picture, simple essay writing skills